Magnetoencephalographic dynamics and adaptive brain networks across multiple timescales - Mandke, Kanad (2020)
The human brain is a complex network of interconnected neurons which function on various scales of time and space. The observable behaviour produced by the human brain is the result of a cascade of several neuronal events that occur over a wide temporal scale. The project investigated processes near the two ends of the temporal scale using magnetoencephalography (MEG), a non-invasive neuroimaging method with high temporal resolution.